The contribution of synchrotron X-ray powder diffraction to modern zeolite applications: A mini-review and prospects - Lo, BTW; Ye, L; Tsang, SCE (Elsevier, 2018)
Synchrotron X-ray powder diffraction has begun to stretch its strategic presence from the sheer determination of crystal structures into the mechanistic and kinetic information of microporous zeolite materials. Not only can this technique be used to reveal the internal framework structure of zeolites and their active sites, but it can also be combined with other analytical tools to suit the particular needs for in situ or operando gas storage and separation and catalytic studies. This review covers the recent development of using synchrotron X-ray powder diffraction as the primary tool for the study of fundamental interactions with organic molecules with active sites in powder zeolites, as well as some perspectives based on this experimental capability.